A novel silica nanowire-silica composite aerogels dried at ambient pressure. (5th February 2017) - Tang, Xiaobing; Sun, Aihua; Chu, Chengyi; Yu, Mingli; Ma, Si; Cheng, Yuchuan; Guo, Jianjun; Xu, Gaojie
Abstract: A novel silica nanowire-silica composite aerogels with excellent thermal insulation and mechanical properties was prepared by adding SiO2 nanowires as a secondary phase into the silica matrix and drying at ambient pressure. The SiO2 nanowires and silica aerogel matrix have outstanding compatibility and dispersibility because the components of nanowire and aerogel matrix all are silica, which contributes to the improvement of the mechanical property of the silica composite aerogels. The physical, mechanical and thermal properties of the SiO2 nanowires based composite silica aerogel are investigated and discussed in detail. The results indicate that the monolithic aerogels with high specific surface area, porosity and large pore volume. The thermal conductivity of the composite silica aerogels only increases gently (0.006 W·m − 1 K − 1 ) as the addition of SiO2 nanowires rises from 0 wt% to 14 wt%, while their mechanical properties have been improved greatly. The SiO2 nanowires based composite silica aerogel would be widely used in the thermal insulation application because of its outstanding thermal insulation property. Graphical abstract: Highlights: A novel silica nanowire-silica composite aerogels was prepared and dried at ambient pressure. The SiO2 nanowire and silica aerogel matrix have excellent compatibility. The SiO2 nanowires need not to be modified before being used to prepare composite silica aerogels. Silica nanowire-silica composite aerogels have outstanding mechanical and thermal insulation properties.